2017
DOI: 10.1177/0312896217729728
|View full text |Cite
|
Sign up to set email alerts
|

Value-creation through spin-offs: Australian evidence

Abstract: We examine announcement effects and the long-run stock performance associated with spin-offs for companies listed on the Australian Securities Exchange. The 3-day announcement effect is a significantly positive 2.93%. Contrary to previous studies, we find no differences between ex post completed and non-completed spin-off announcements. The abnormal returns do not seem to be related to factors found significant in previous studies, such as an increase in industrial or geographical focus, information asymmetry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…A good number of studies have been conducted to date to examine the reaction of the capital markets to the spin-off of companies . These studies are consistent in their conclusion that this form of corporate restructuring leads to the positive response of shareholders on the announcement of this event (Ball et al ., 1993;Chai et al ., 2018) but draw inconclusive substantiation to elucidate the sources of gains to the shareholders (Ahn and Denis, 2004;Chemmanur et al ., 2014;Habib et al ., 1997;Maxwell and Rao, 2003) . Furthermore, whether spin-offs succeed in the creation of wealth for shareholders in the long-run periods is a debatable issue in the community of academicians (Chong et al ., 2009;Cusatis et al ., 1993;Murray, 2008;Veld and Veld-Merkoulova, 2004) .…”
Section: Theoretical and Empirical Evidence In The Appraised Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…A good number of studies have been conducted to date to examine the reaction of the capital markets to the spin-off of companies . These studies are consistent in their conclusion that this form of corporate restructuring leads to the positive response of shareholders on the announcement of this event (Ball et al ., 1993;Chai et al ., 2018) but draw inconclusive substantiation to elucidate the sources of gains to the shareholders (Ahn and Denis, 2004;Chemmanur et al ., 2014;Habib et al ., 1997;Maxwell and Rao, 2003) . Furthermore, whether spin-offs succeed in the creation of wealth for shareholders in the long-run periods is a debatable issue in the community of academicians (Chong et al ., 2009;Cusatis et al ., 1993;Murray, 2008;Veld and Veld-Merkoulova, 2004) .…”
Section: Theoretical and Empirical Evidence In The Appraised Studiesmentioning
confidence: 99%
“…A mass of studies has acknowledged the positive impact of spin-off announcements on stock prices all over the world (Blount and Davidson, 1996;Harris and Glegg, 2008;Parrino, 1997;Seifert and Rubin, 1989;Veld and Veld-Merkoulova, 2004) despite the variations in methodology, sample period, and the variables studied for explaining the gains to the shareholders (Burch and Nanda, 2003;Denning, 1988;Krishnaswami and Subramaniam, 1999;Slovin et al ., 1995;Veld and Veld-Markoulova, 2008) . Most of these studies come from the USA (Feng et al ., 2015;Miles and Rosenfeld, 1983;Rosenfeld, 1984;Seward and Walsh, 1996;Wheatley et al ., 2005), and, though comparatively small in number, studies from Europe (Murray, 2008;Veld and Veld-Merkoulova, 2004) and Asia-Pacific have also begun to emerge (Aggarwal and Garg, 2019;Chai et al, 2018;Padmanabhan, 2018) .…”
Section: Spin-off Announcements and The Stock Pricesmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to these benefits, most empirical studies based on firms in developed economies have found that divestiture announcements increase the short‐run shareholder wealth of parent firms (e.g., Allen, 2001; Bergh et al, 2008; Chai et al, 2018; Depecik et al, 2014; Dittmar & Shivdasani, 2003; John & Ofek, 1995; Rosenfeld, 1984) and consecutive accounting performance of parent firms (e.g., Bergh, 1998; Brauer et al, 2017; Cho & Cohen, 1997; Hoskisson & Johnson, 1992; Markides, 1995). Only a handful studies have noted a negative short‐run shareholder wealth (Wright & Ferris, 1997) or a lack of evidence to support value‐creation through divestiture events for parent firms (Denning & Shastri, 1990; Marquette & Williams, 2007; Vijh, 1994).…”
Section: Introductionmentioning
confidence: 99%